The Guidelines for Developing Ethnicity Parents’ Participation in Primary School, Tha Song Yang District, Tak - Moungmaithong, Wachirut; Saengseemuk, Suraphong (Journal of Buddhist Education and Research (JBER), 2025)
This research with three objectives: 1) to examine the current and problems of ethnic student parent participation in primary schools, 2) to find guidelines for ethnic student parent participation in primary schools, and 3) to assess guidelines for developing ethnic student parent participation in primary schools in Tha Song Yang District, Tak Province. The sample and data sources used in this research were 361 parents of students in grades 4 to 3 in primary schools in Tha Song Yang District, Tak Province, academic year 2024. The instruments used were questionnaires, interview forms, and feasibility and appropriateness assessment forms. Data were analyzed by finding percentages, frequencies, means, standard deviations, and content analysis. The research results found that the participation of ethnic students’ parents in primary schools in Tha Song Yang District, Tak Province was at a high level overall and in each aspect. The participation problems were found to be most academic, followed by student affairs, budget, and quality assurance, respectively. The participation guidelines were found to be academic, namely that educational institutions should allow communities to participate in meetings, planning, and monitoring the implementation of guidelines for setting school standards. The budget, namely that educational institutions should request budgets from private sectors, foundations, shops, and Kathin robe offerings. The student affairs, namely that educational institutions should provide opportunities for communities and students to participate in policy-making and various activities in the school. The quality assurance, namely that educational institutions should organize teachers to work with the community to develop research tools, emphasizing knowledge, skills, and abilities in quality assurance. The evaluation results of the feasibility and appropriateness of the participation development guidelines found that the overall feasibility was at a high level. Student affairs was at the highest level with an average value at the highest level. The next was quality assurance with an average value at a high level. The budget had an average value at a high level. The academic aspect had an average value at a high level and the lowest level, respectively. As for the appropriateness, it was found that the overall appropriateness was at a high level. Student affairs was at the highest level. The average value is at the highest level, followed by the quality assurance aspect with a high average value, the budget aspect with a high average value, and the academic aspect with a high average value, and the lowest average value, respectively.